The Role of Leadership Style on Employee Voice Behavior and Satisfaction - Mohammed L. Bello; Abdulrazaq K. AbdulKareem; Abdulrasaq A. Ishola; Isa Omolabi; Rasaq Salman (Cihan University-Erbil Journal of Humanities and Social Sciences)
This research examined a model linking leadership style to employee voice behavior, self-efficacy, and job satisfaction. Data from 125 employees in the selected ministries and agencies in Kwara State were analyzed using partial least square-structural equation modeling. Results demonstrated that empowering leadership style positively predicted employee voice. In turn, increased voice opportunities reinforced employee self-efficacy tied to enactive mastery experiences. Employees who had input opportunities gained confidence in their capabilities. Finally, elevated self-efficacy perceptions mediated a positive relationship between employee voice and job satisfaction, conveying perceived control and competence. Findings suggest that a supportive leadership foundation transforms an upward spiral wherein involvement shapes affirming self-perceptions, fuelling workplace satisfaction. This study quantifies mediating mechanisms flowing from leadership style through voice participation and efficacy in ultimately predicting work satisfaction essential forpublic sector human capital development and accountability.